Pengaruh Social Proof dan Kualitas Visual Konten TikTok Shop terhadap Minat Beli dengan Promotional Overload sebagai Variabel Moderasi pada Generasi Z - Rafif Muhammad Hirsya; Hujjatullah Fazlurrahman; Ika Diyah Candra Arifah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Digitalization shifts consumer behavior. This study aims to analyze the effect of social proof and visual content quality on Gen-Z's purchase intention on TikTok Shop, with promotional overload as a moderating variable. The research utilizes a quantitative approach with purposive sampling, collecting data from 204 Gen-Z TikTok Shop users via an online questionnaire. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. The general findings indicate that both social proof and visual content quality significantly and positively influence consumer purchase intention. Furthermore, promotional overload is found to significantly moderate and weaken the positive effects of both independent variables on purchase intention. In conclusion, while social proof and attractive visuals are critical in driving digital sales, excessive promotional exposure can diminish consumer interest due to information fatigue.